HIV-1 infection, but not syphilis or HBV infection, is a strong risk factor for anorectal condyloma in Asian population: A prospective colonoscopy screening study. (August 2015) - Nishijima, Takeshi; Nagata, Naoyoshi; Watanabe, Kazuhiro; Sekine, Katsunori; Tanaka, Shohei; Kishida, Yoshihiro; Aoki, Tomonori; Hamada, Yohei; Yazaki, Hirohisa; Teruya, Katsuji; Gatanaga, Hiroyuki; Kikuchi, Yoshimi; et al.
Highlights: We prospectively screened anorectal condyloma with high-resolution colonoscopy. The association between anorectal condyloma and sexually transmitted infections were investigated. HIV-1 infection was strongly associated with anorectal condyloma. Syphilis or HBV infection was not associated with condyloma. Positive anal HPV 16/18 was associated with condyloma in HIV-1-infected patients. Summary: Objective: To investigate the association between anorectal precancerous lesions, including condyloma, and sexually transmitted infections (STI) in Asian population. Methods: This prospective study enrolled 2677 patients who underwent high-resolution colonoscopy for anorectal cancer screening. Anorectal lesions were diagnosed based on endoscopic findings and confirmed by biopsy. The association of HIV-1 infection, syphilis, and HBV infection with anorectal lesion was estimated by multivariate logistic regression. In HIV-1-infected patients (n=244), anal canal HPV-DNA was screened and genotyped. Results: Although no malignancy was identified, anorectal condyloma was diagnosed in 32 (1.2%) male patients. 41% of anorectal condyloma cases had no specific lower GI symptoms. Multivariate analysis identified HIV-1 infection, but not syphilis or HBV infection, as an independent significant factor for condyloma (OR: 176.5, 95%CI 22.52-1383, p<0.001). In HIV-1 infected patients, positive type 16/18 HPV-DNA (OR: 4.766, 95%CI 1.838-12.36, p=0.001), lower CD4 cell count (per 100/μl decrement, OR: 1.056, 95%CI 1.056-1.587, p=0.013), and current smoking (OR: 3.828, 95%CI 1.486-9.857, p=0.005) were independently associated with anorectal condyloma. Conclusions: HIV-1 infection, but not syphilis or HBV infection, was identified as a strong risk for anorectal condyloma. Anal HPV 16/18 was highly prevalent in patients with HIV-1 infection, especially in those with condyloma.